2010
DOI: 10.1093/aob/mcq110
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of maternal and paternal effects on embryo and seed development in wild radish (Raphanus sativus)

Abstract: The expected maternal effects on embryo development were observed, but there was also evidence for an early paternal role. The relative effects of these controls may change over time. Thus, there may be times in development when selection on the maternal, paternal or embryo contributions to development are more and less likely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 75 publications
2
27
0
1
Order By: Relevance
“…In contrast, the pollen donor diversity in Rhamnus alpinus has been reported to affect on different reproductive components of F 1 progeny e.g. embryo size (Nakamura and Stanton, 1989), seed size, germination rate, seedling vigor and survivorship (Banuelos and Obeso, 2003), and the embryos developments (Diggle et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the pollen donor diversity in Rhamnus alpinus has been reported to affect on different reproductive components of F 1 progeny e.g. embryo size (Nakamura and Stanton, 1989), seed size, germination rate, seedling vigor and survivorship (Banuelos and Obeso, 2003), and the embryos developments (Diggle et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…For instance, in Raphanus sativus seed growth rate (Diggle et al, 2010), and embryo/seed development rate (Marshall and Diggle, 2001) were shown to be affected by both maternal and paternal parents. This simultaneous impact of both paternal and maternal on progeny performance indicates genotypic interactions (Marshall et al 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Mizrahi et al, 2004), mentimun (Olfati et al, 2010), durian (Indriyani et al, 2012), Arabidopsis thaliana (Andriotis et al, 2012), apel (Militaru, Butac, Sumedrea, & Chi, 2015), Brassica napus (Li et al, 2015), dan tomat (Piotto, Batagin-Piotto, de Almeida, & Oliveira, 2013;Rahaii et al, 2016). Pada persilangan lobak liar (Raphanus sativus), tetua betina berpengaruh terhadap perkembangan embrio, namun pengaruh tersebut sangatlah bergantung pada peran tetua jantan sebagai donor tepung sari dan peran tetua jantan tersebut dapat berubah-ubah setiap saat (Diggle et al, 2010). Kondisi tetua betina karena adanya cekaman faktor lingkungan, seperti terjadinya kekurangan air, berpengaruh terhadap proses perkembangan buah dan biji karena menurunnya sumber-sumber energi yang diperlukan bagi proses perkembangan buah dan biji (Gehring & Delph, 2006).…”
Section: Hasil Dan Pembahasan Pengaruh Tetua Jantan Terhadap Karakterunclassified
“…For example, when resources are limited plants produce smaller seeds (Vaughton and Ramsey 1997) or abort seeds selectively (Stephenson 1981, Sun et al 2004, Wise and Cummins 2006. Paternal identity and pollen traits have indeed been shown to affect seed traits (Diggle et al 2010).…”
mentioning
confidence: 99%